HUBUNGAN KECEPATAN DAN PANJANG TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS XI TKJ 1 SMK MUHAMADIAH 3 TERPADU PEKANBARU - ', Samsurizal; ', Drs. Ramadi,S.Pd, M.Kes, AIFO; Juita, S.Pd. M.Pd, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The problem of this research is not optimal about speed and leg length with the result of long jump squat style. This research is conducted to determine whe ther there is a relationship speed and leg length with the result of long jump squat style in male students class XI TKJ 1 SMK 3 Terpadu Pekanbaru. Sample in this research is male students class XI TKJ 1 SMK 3 Terpadu Pekanbaru. A sampling technique that only male students sampled (purposive sampling). Instruments performed in this study is running speed of 30 meters test are intended to measure a person speed , then test for leg lengh which aims to measure the leg length persons. Then test for long jump squat style, which aims to measure the far leap persons. After that, statistical data processed, normality test with lilifor test at significant level a0,05. Based from the research, it can take the following conclusion. Of the result obtained running speed of 30 meters did not have a significant relationship with long jump results in male students class XI TKJ 1 SMK 3 Terpadu Pekanbaru because rcount(0,410) < rtab (0,456), from the results leg length have a significant relationship with long jump result in male students class XI TKJ 1 SMK 3 Terpadu Pekanbaru because rcount(0,382) < rtab (0,456), have a significant relationship together between running speed of 30 meters and leg length with long jump result in male students class XI TKJ 1 SMK 3 Terpadu Pekanbaru because rcount(0,539) < rtab (0,456).Key Words : Speed, Leg Length, Long Jump Squat Style.